Benefits of Using Artificial Intelligence Tools in Education - Осонду, Джеймс (Научни трудове, 2024)
Artificial intelligence (AI) is impacting education in many ways. From virtual assistants for personalized education, to student or teacher tracking systems, the potential benefits of AI for education often come with a discussion of its impact on privacy and well-being. At the same time, the social transformation brought about by AI requires reform of traditional education systems. in this study, A comparative analysis methodology was made in this study, and the best free tools under 10 categories regarding education were identified to view their similarities and differences. The focus of the study was on the benefits these tools regarding the needs of students.
Keywords: Изкуствен интелект; Инструменти; Обучение; ИИ